THE EFFECT OF ELECTRONIC WORD OF MOUTH AND BRAND IMAGE TOWARDS PURCHASE INTENTION ON WARDAH LIPSTICK IN PONTIANAK - admin, ANANDA ARCHIE B12112025 (Jurnal Manajemen Update, 2016)
In this globalization era, the increasing use of internet has caused many people to deliver their message, impression and thought through the internet, such as social media. Traditionally, word of mouth is a form of communication which delivers a message from one person to other people directly and continuously. Nowadays, however, there is electronic word of mouth transmission that is fast and comes in a big scale. Brand image is the image or perception which exists in the customers’ mind. Purchase intention is the willingness of a customer to buy a product. The purpose of this study is to analyze the impact of electronic word of mouth on purchase intention through the brand image as a mediator variable by using lipstick Wardah research object. The sample of this research is female, 17-50 years old, who has knowledge about Wardah lipstick, uses social media and is domiciled in Pontianak. The data are obtained by using questionnaire. This research uses purposive sampling, which total sample is 100, and SPSS 17 to process the data. The result of the research shows that there is a significant positive and relationship between the electronic word of mouth on brand image and purchase intention. The effect of electronic word of mouth towards brand image is 68,2%, electronic word of mouth towards purchase intention 15,8%, brand image towards purchase intention 71,4%. Keyword: Electronic Word of Mouth, Brand Image, Purchase Intention